Retarding effect of concentration of cementation solution on biocementation of soil - Lai, Han-Jiang (2022)
Concentration of cementation solution (CCS) is one of the key factors influencing the cementation effect on soil improvement through the microbially induced carbonate precipitation (MICP) process. To precipitate more calcium carbonate per treatment, a higher CCS is needed. However, the MICP process may be retarded or even terminated with an increase in CCS. This retarding effect can be a major limitation for the MICP-based soil treatment and thus needs to be understood properly. This paper presents a systematic study on the conditions causing retarding and its effect on biocementation. The test results of this study have identified that there is retarding effect of CCS on the MICP process, showing that the calcium conversion efficiency, which represents the amount of calcium that has been converted into calcium carbonate in each treatment, reduces with the increase in CCS, and the concentration of calcium is the control factor. The retarding effect will dominate increasingly when CCS is higher than 1.0 M and the amount of calcium carbonate precipitation will reduce for the given amount and type of bacteria used in this study and become zero with CCS of 2.5 M. For the same calcium carbonate content, the unconfined compressive strength is greater for sand treated using a lower CCS as the contribution to the bonding strength by the calcium carbonate generated under a lower CCS is greater than that under a higher CCS.